University teachers’ professional vision with respect to their conceptions of teaching and learning: findings from an eye-tracking study - Heinonen, Neea; Katajavuori, Nina; Södervik, Ilona (Frontiers in Education, 2023)
This study investigated how university teachers’ (mis)conceptions of teaching and learning are related to their ability to notice and interpret pedagogically significant incidents in the classroom, that is their professional vision. Additionally, we examined whether university teachers can be supported in their development of conceptual understanding and professional vision through a short pedagogical training. A total of 32 university teachers who participated in this study completed a teacher conception questionnaire and an eye-tracking measurement with a stimulated retrospective recall (SRR) interview. A pre-test / post-test design was utilized. The findings indicate that in general, professional vision scores and (mis)conceptions of teaching and learning did not correlate. However, with regard to classroom incidents where teachers’ visual attention needed to be selectively allocated due to simultaneous interactions, university teachers with more misconceptions and less sophisticated conceptions of teaching and learning tended to focus on the teacher’s actions in the classroom. By contrast, university teachers with fewer misconceptions and with more sophisticated conceptions of teaching and learning tended to focus on students’ actions. University teachers less sophisticated conceptions became more sophisticated as a result of pedagogical training. Additionally, statistically significant improvements in participants’ noticing were identified, but interestingly not in their interpreting skills. The results emphasize the relevance of the need for pedagogical training and the development of conceptual understanding for university teachers in relation to learning theories in order to support their pedagogical expertise as well as their professional vision.